W świecie kolorowej (anty)utopii. O animowanych cyborgach w Kongresie Ariego Folmana - Woroch, Adrianna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article focuses on pointing out the functions of using animation technique and elements of the science fiction genre in Ari Folman’s The Congress from 2013. The film, which is loosely based on the short story The Futurological Congress by Stanisław Lem, balances on the edge of various genres, using the techniques of both live action film and computer animation. Folman proposes a glamorous, colorful vision of an (anti)utopian future, in which pharmacologically-modified cyborg-people participate in a collective hallucination, which is an alternative reality to the post-apocalyptic real world. The director makes several significant changes to the original, thanks to which he introduces a universal message and asks questions which seem far more relevant in the context of both contemporary culture and the environmental crisis that can no longer be ignored (although the issue of an impending natural disaster was also important in Lem’s works).